Suitability of hepatocyte cell lines HepG2, AML12 and THLE-2 for investigation of insulin signalling and hepatokine gene expression. Issue 10 (24th October 2018) - Sefried, Stephanie; Häring, Hans-Ulrich; Weigert, Cora; Eckstein, Sabine S.
Abstract : Abstract : Immortal hepatocyte cell lines are widely used to elucidate insulin-dependent signalling pathways and regulation of hepatic metabolism, although the often tumorigenic origin might not represent the metabolic state of healthy hepatocytes. We aimed to investigate if murine cell line AML12 and human cell line THLE-2, which are derived from healthy liver cells, are comparable to hepatoma cell line HepG2 for studying acute insulin signalling and expression of gluconeogenic enzymes and hepatokines. Insulin responsiveness of AML12 and THLE-2 cells was impaired when cells were cultured in the recommended growth medium, but comparable with HepG2 cells by using insulin-deficient medium. THLE-2 cells showed low abundance of insulin receptor, while protein levels in HepG2 and AML12 were comparable. AML12 and THLE-2 cells showed only low or non-detectable transcript levels of G6PC and PCK1 . Expression of ANGPTL4 was regulated similarly in HepG2 and AML12 cells upon peroxisome proliferator-activated receptor δ activation but only HepG2 cells resemble the in vivo regulation of hepatic ANGPTL4 by cAMP. Composition of the culture medium and protein expression levels of key signalling proteins should be considered when AML12 and THLE-2 are used to study insulin signalling. With regard to gluconeogenesis and hepatokine expression, HepG2 cells appear to be closer to the in vivo situation despite the tumorigenic origin.